Students’ engagement in school, achievement goals and grade level: A literature review. - Veiga, Feliciano (2015)
Framework: Students’ Engagement in School (SES) is regarded in the literature as a valuable cutting-edge construct, although few empirical studies address its relationship with personal variables, such as achievement goals, attending, for instance, to the students’ grade levels. Purpose: The present research sought to examine studies on the relation between achievement goals and school variables as students’ engagement in school, over adolescence. Method: In order to describe the state of art of student’s engagement in school and achievement goals and grade level, we prepared a narrative review. Conclusions: The studies revised highlight the role of achievement goals as important for a student’s engagement in school; however, there is the need to extend research in this area by considering potential personal and school-related mediator variables. It is suggested a special support for those students who, exhibiting an academic difficulties pathway, also lack academic goals and strategies, resulting in low engagement in school and, therefore, low achievement and a higher probability of dropping out. There is the need to extend research in this area by analyzing the variables achievement goals and student’s engagement in school, along with the relations between these variables. An intervention to support students little achievement goals in studies of quasi-experimental nature, is also inferred from the studies revised. The activation of appropriate achievement goals emerges as a way to promote students’ engagement in school and, thus, as a strategy of great importance to be considered in the education of teachers and psychologists.